Pengaruh Tingkat Konsentrasi dan Lamanya Inkubasi EM4 Terhadap Kualitas Organoleptik Pupuk Bokashi - Kastalani Kastalani (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
The research takes location at Jl. A. Yani Km.85 Binuang. The aim of the research was to study the interaction between consentration and incubation period of EM4 on the quality of bokashi. This research used factorial of Completely Random Design (CRD) with two factors. The first factors are: contentration 0.05%, concentration 0.1%, concentration 0.2% and concentration 0.4%. While the second factors are: incubation period 4 days, incubation period 7 days and incubation period 10 days. The organoleptic test showed that the concentration and incubation period no significant effect on color, smelt and texture. Key words : Bokashi, effective microorganism, concentration, incubation.